The Enforcement of Criminal Law in the Utilization and Management of Forest Area Having Impact Toward Global Warming - Ifrani Ifrani; Yati Nurhayati (Sriwijaya Law Review, 2017)
The rampant corruption is in the utilization and its influence on global warming. It is expected in the future, in addition to the availability of maps of forest area easily accessible with some clear regional boundaries, there are also institutional and human resource capacity strengthening in the areas permitting the process to prevent corruption in the management of forest areas in Indonesia resulted in the destruction of natural resources, especially forests. Various activities in that sector become a critical point of the occurrence of corruption cases. In addition to the inadequacy of the forest area maps, unclear set of area boundaries, and the violations of licensing criteria, the cases of illegal logging become the factors that cause damages to the forest land in Indonesia. The purpose of this paper is to find out the relationship between corruption in the permitting conversion of forest land field of the ministry. The method used in this study was descriptive analytical research describing and analyzing the available facts in accordance with the issue that became the object of the research study.